The weight - Mendes, Melissa (Drawn & Quarterly, 2025)
"A rural family's cycle of love, loss, and renewal, set against the beauty and adversity of mid-century America. Edie comes into the world calmly as the adults around her rage. Her father is a cruel man who beats her mother regularly and much of Edie's young life is spent trying to escape this tyrant. "Why doesn't she ever cry?...Gives me the creeps." Of course, being a child means she lives a child's life--she still has laughter-filled sleepovers and outdoor adventures with the local rat pack of kids still too young to work. But Edie's heart grows callous as her father becomes drunker and angrier. Melissa Mendes' pastoral cartooning captures the openness of rural America--soft breezes, tall grass, whirring grasshoppers, rainstorms, skinned knees. But all the while, the cruelty, the disappointment of man lurks behind the barn and in the trailer. Life can be stubbed out as easily as a cigarette tossed in the dirt. One moment all focus, next, gone without a thought. Will Edie find herself repeating a cycle or will she be free like she felt as a child?"--Amazon.com.